La suerte del enano: Translating paremias into Italian - Morabito, Stefano (Romanica Olomucensia, 2024)
The translation of paremias in literary texts is a challenge for the translator, even in the case of related languages. This article analyses the Italian translation of the paremias that are used in César Pérez Gellida's La suerte del enano. This work has been chosen because Pérez Gellida makes such extensive use of paremias in his novels that this can be considered one of their characteristics, and because it is his first work to have been translated into Italian. For the purposes of the study, paremias were extracted from the original text and catalogued, and it was noted that there are also deautomatisations and some 'invented' paremias or so-called pseudoparemias; finally, the translation made for the Italian edition was analysed. The results point to occasional difficulties in translating paremias that lack an exact equivalent in the target language and in respecting the functions they perform in the text, as in the case of the paremia that gives the novel its title. On the other hand, the best results were obtained when the translator was creative. In conclusion, the translation of paremias is an aspect that the translator cannot avoid, especially in the case of authors in whose works they play an important role. For this to happen, a long documentation work in the repertoires in search of correspondences is necessary, although sometimes it is necessary for the translator to be creative and take the risk of 'creating' a paremia.
Keywords: paremia; noir novel; Pérez Gellida; Spanish to Italian translation